Design of Bacteria Bottle Clamping Elements Based on Regression Models - Wenshuo Gao; Weidong Song; Tianhang Ding; Jiaoling Wang (Journal of Mathematics)
The fixture design of the bacteria bottle plays a vital role in designing a bottled fungus picking robot to save labor cost in the picking process of bottled fungus. This paper proposed a kind of clamping element design method based on regression models. Several sets of clamping elements were designed according to the appearance data of bacteria bottle. A single-factor test was conducted by using these clamping elements, and three levels of every factor were selected to obtain the desired values of clamping elements. Then, a Box–Behnken test was performed by selected levels. The established regression models described a numeric relationship between the variation of vital measurement points and all variation sources under a precise clamping element layout. To solve the problems in obtaining the direct parameters, a response surface method was presented based on the regression models. Finally, a test was used to demonstrate the effect of the optimized clamping elements when clamping a bacteria bottle. Through the related analysis and optimization, it was demonstrated that the holding effect of the clamping elements was the best under these conditions: the inner arc area was 4948 mm2; the downward displacement was 1.48 mm; and the rubber thickness was 3.69 mm. It showed that the proposed method was feasible, and the assembly quality after optimizing had been greatly improved. It can provide a reference for designing the bottle fixture of a picking machine.